Admixture Mapping of Prostate Cancer in African Americans participating in the North Carolina-Louisiana Prostate Cancer Project (PCaP) - Bensen, Jeannette T. (2013)
BACKGROUND: Few genetic risk factors have been uncovered that contribute specifically to the racial disparity in prostate cancer (CaP) observed in African Americans (AA). With the advent of Ancestry Informative Marker (AIM) single nucleotide polymorphism (SNP) panels and powerful genetic strategies such as Mapping by Admixture Linkage Disequilibrium (MALD) it is possible to discover genes that underlie ethnic variation in disease risk. METHODS: 1130 AA CaP cases enrolled in the North Carolina-Louisiana Prostate Cancer Project (PCaP) were genotyped using a 1,509 AIM SNP panel. MALD was performed using ADMIXMAP to test for linkage between CaP risk and ancestry estimates at each AIM SNP. RESULTS: The largest increase of African ancestry was observed at marker rs12543473 (P=0.0011), located on chromosome 8q24.21, and the greatest excess of European ancestry was observed at marker rs10768140 (P=0.0004) at chromosome 11p13. CONCLUSIONS: The study confirmed the 8q24 risk loci and identified a novel genomic region on 11p13 that is associated with CaP risk. These findings should be replicated in larger AA populations and combined with fine mapping data to further refine the novel 11p13 CaP risk loci.